What is Lost in "Restoring Truth and Sanity:" Queer Approaches to Absence, Silence, and Erasure in Archival Description - Evan M Allgood; Travis L Wagner (The Political Librarian, 2025)
Since Trump’s second inauguration, over a dozen executive orders have been established that aim to terminate diversity, equity, and inclusion (DEI) policies and programs, deter the use of inclusive language, and strip away human rights. These executive orders have impelled memory workers to revise the historical record at vital institutions like the Stonewall National Monument and the Smithsonian Museums and to remove previously public data and history from government sites. This is far from the first time forces outside of the archival profession have urged the re-writing, simplification, or erasure of complex histories, nor is it the first time archival practitioners have resisted. We combine findings from two projects—qualitative interviews with archival practitioners and an analysis of geographically-specific queer collections—to surface critical acts of resistance performed by archival practitioners that refuse the erasure of LGBTQIA+ history and reject the fallacy of archival neutrality. Further, our findings suggest that, even in an era of active archival erasure that uniquely impacts LGBTQIA+ communities, the role of archival silence and invisibility is complex and hardly a binary of presence and absence. Based on these findings, we call for a de-centralized and de-politicized archival processing: one that does not bend to partisan whims, but instead prioritizes the voices of those whose materials they are collecting. While our research is specific to LGBTQIA+-related collections, our findings can direct us towards broader, everyday acts of resistance possible within the modern archival profession.
Keywords: LGBTQ+ Communities; Archives; Archival Neutrality; Archival Erasure; Qualitative Research